Regulation and Macroeconomic Performance - Goff, Brian L.; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 1996)
This project grew out of a recognition that I could fmd no aggregate measure of the amount of regulation beyond crude proxies such as the number of pages in the Federal Register. As I began to address this specific issue. I became much more aware of two things -- the enormity of regulation in the u.s. economy and the relative absence of economic research into the macroeconomic consequences of those regulations. While I would have readily granted the idea that many economist'> knew more about regulation than I did, I would have thought my knowledge of regulation to be at least up to the average economist's. My graduate training in the early to mid 1980s included special attention to the field of "public choice" and related topics, all of which occasionally explored regulatory topics. Moreover. I had at least a passing knowledge of the debates concerning deregulation in the late 1970s and early 1980s. Because of this, my own ignorance of regulation's actual expanse and its aggregate consequences startled me and heightened my interest in expanding empirical research into regulation as a macroeconomic influence. The more I thought about graduate macroeconomics classes and texts, the more that I realized the exclusion of regulation as a macroeconomic topic in spite of its massive scale and far-reaching tentacles.
1 Government Regulation and Economics -- Defining Regulation -- Economists and Government Policy -- Key Issues -- Overview -- 2 Understanding Regulation$1 (Bs Macro Effects -- Channels of Regulatory Influence -- From Micro to Macro Effects -- Subjective Welfare Gains and Losses -- Summary -- 3 A Tour of the Regulatory Sprawl -- Regulatory Volatility Since 1950 -- Regulatory Breadth -- Regulation$1 (Bs Breadth from a Supply/Demand Perspective -- Summary -- 4 Regulation Versus other Government Policies -- Government Spending -- Deficits -- Government Spending Revisited -- Taxes -- Monetary Policy -- Summary -- 5 Past Studies of Regulation$1 (Bs Macro Effects -- Expenditure Studies -- Industry/Regulation-Specific Econometric Studies -- Macro-Model and General Equilibrium Studies -- Capital Market Studies -- Government Budget Studies -- Compilations -- Critical Measurement Issues: A Macro View -- Summary -- 6 An Index of Regulation -- Regulation as a Latent Variable -- The Logic of Factor Analysis -- Variables Related to Effective Regulation -- The Effective Regulation Index (ERI) -- Summary -- 7 The Regulatory Index and Macro Performance -- Macroeconomic Performance Measures -- Time Series Analysis of ERI$1 (Bs Impact -- How Big Are the Effects? -- Accounting for the Slow Growth 1970s -- Including Oil Price and General Government Spending Effects -- Summary -- Appendixes -- 8 Why Regulation? -- ERI by Presidential Administration -- ERI and Congressional Control -- Forces Behind the Lawmakers -- Examples from Earlier Regulatory Waves -- The 1960s and 1970s -- Deregulation in the Early 1980s -- Politics and the Future of Regulation.s
Keywords: Industrial organization; Macroeconomics; Political science; Industrial Organization; Macroeconomics/Monetary Economics//Financial Economics; Political Science